Educação Freireana : axiologia crítica no currículo de Biologia - Demartini, Gabriel Ribeiro (2024)
The present work was configured as qualitative research, based on the assumptions of historical-dialectical materialism. The research problem that guided the investigation originated from questions about the historically existing ideological transgression between knowledge and values, manifested by banking education. Thus, the objective was to understand and develop the interface between ethics and knowledge in the transformative curricular praxis in biology teaching, based on Freirean pedagogy. To this end, an investigative dive into philosophical modernity was necessary, as a privileged place for understanding this axio-epistemological fracture, explaining the reduction that scientific knowledge has suffered, making it uncommitted to humanization. Based on critical reflection on a curriculum construction experience based on the Freirean thematic investigation process, carried out in a state school in São Francisco do Brejão – MA, we sought to understand the axiological (ethical and political) and epistemological aspects present in educational practice. The categories ethical-critical alterity and ontological negativity, both based on Dussel, and Freirean dialogicity were developed as analytical parameters, enabling the understanding of the axio-epistemological inseparability of ethical-critical orientation in curricular praxis by the generative themes. In short, they denounced the negativities that generated the concrete victims of the sociocultural organization and made it possible, through recognition of the Other, to regain protagonism in the political struggle for life. Furthermore, the dialectical and dialogical overcoming of banking education through curricular construction via a generative themes made it possible to announce a theoretical-methodological path committed to humanization.